ANALYSIS OF FACTORS INFLUENCING THE PERFORMANCE OF NATIONAL PRIVATE BANKING IN INDONESIA, MODERATED BY THE USE OF FINTECH - Maretta Yuraska Sinulingga; Khaira Amalia Fachrudin; Nisrul Irawati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The purpose of this study is to analyze the "Analysis of Factors Influencing the Performance of National Private Banking in Indonesia, Moderated by the Use of Fintech." The data collected in this study are secondary data, gathered from the financial reports of national private banks for the 2020-2024 period. The sample in this study is 140. This study uses quantitative data. The data analysis technique used panel data regression analysis with the help of eViews software. The test results show that the Loan to Deposit Ratio has a significant effect on Return on Assets at National Private Banks in Indonesia. Operating Expenses/Operating Income has a significant effect on Return on Assets at National Private Banks in Indonesia. Non-performing Loans have a significant effect on Return on Assets at National Private Banks in Indonesia. The Loan to Deposit Ratio and Operating Expenses/Operating Income have a significant effect on Return on Assets, with fintech as a moderating variable. Non-performing Loans do not have a significant effect on Return on Assets, with fintech as a moderating variable at National Private Banks in Indonesia.